Edge Detection Algorithms in Mapping the Condition and Historic Phases of the Last Judgment Mosaics in Torcello/Venice - Stoyanova, Magdelena; Pavlova, Lilia (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2019)
Whenever innovative survey techniques allow gathering detailed information about fixed building interiors, establishing the conditions, authenticity or the structural problems of historic built in mosaics rests a quite complex process. This paper analyzes the reliability of digital post processing techniques to support distinguishing among application methods, original and remade areas, and for detailed damage assessment. The results are destined to form an interdisciplinary repository regarding the Byzantine mosaics of Torcello as hearth of the Veneto-Byzantine mosaic school of the 13th c.